2006
DOI: 10.1111/j.1525-1594.2006.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Leakage Flow in Centrifugal Blood Pumps

Abstract: This article presents a new approach in determining the functional relationship between the leakage flow in a centrifugal blood pump and various parameters that affect it. While high leakage flow in a blood pump is essential for good washout and can help prevent thrombus formation, excessive leakage flow will result in higher fluid shear stress that may lead to hemolysis. Dimensional analysis is employed to provide a functional relationship between leakage flow rate and other important parameters governing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Speed modulation was only used in the outflow banding mode to ensure minimum pump speed remained within the speed limits of the VentrAssist device. Operating the pump below the designed speeds may promote thrombus formation and impeller touch down in pumps with hydrodynamic bearings . Meanwhile, our study only evaluated speed modulation with a VentrAssist pump, which is no longer commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Speed modulation was only used in the outflow banding mode to ensure minimum pump speed remained within the speed limits of the VentrAssist device. Operating the pump below the designed speeds may promote thrombus formation and impeller touch down in pumps with hydrodynamic bearings . Meanwhile, our study only evaluated speed modulation with a VentrAssist pump, which is no longer commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…(8), a reduction in clearance gap size decreases the leakage flow rate, essentially improving pump efficiency. A higher level of pump performance for smaller clearance gaps has also been reported using the method of dimensional analysis (9).…”
mentioning
confidence: 88%
“…Weng‐Kong Chan and Yew‐Wah Wong (20) of the Nanyang Technological University (Singapore) investigated, using dimensional analysis, the functional relationship between the leakage flow (for washout) in a centrifugal blood pump and various parameters that affect it. Results showed that pump performances with a smaller gap clearance were superior compared with those of pumps with larger gap clearances but of similar design.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%